2020
DOI: 10.1016/j.cmi.2020.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of infective endocarditis after transcatheter aortic valve implantation versus surgical aortic valve replacement

Abstract: Objectives: Transcatheter aortic valve implantation (TAVI) is an alternative to surgical aortic valve replacement (AVR) in aortic stenosis (AS). Infective endocarditis (IE) in patients with prosthetic heart valves is associated with significant morbidity and mortality. Data on the incidence, risk factors, and outcomes of IE after TAVI are conflicting. We evaluated these issues in patients with percutaneous TAVI vs. isolated surgical AVR (SAVR) at a nationwide level. Methods: Based on the administrative hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 31 publications
2
28
1
Order By: Relevance
“…There were 106 fulltext articles assessed for eligibility after screening titles and abstracts, and we identified 35 studies that reported the incidence of PVE after TAVR. Finally, 8 articles [Kolte 2018;Amat-Santos 2015;Olsen 2015;Bjursten 2019;Fauchier 2020;Tabata 2020;Butt 2019;Regueiro 2016] were ultimately included in the present systematic review and metaanalysis. The main characteristics and the overall quality of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 106 fulltext articles assessed for eligibility after screening titles and abstracts, and we identified 35 studies that reported the incidence of PVE after TAVR. Finally, 8 articles [Kolte 2018;Amat-Santos 2015;Olsen 2015;Bjursten 2019;Fauchier 2020;Tabata 2020;Butt 2019;Regueiro 2016] were ultimately included in the present systematic review and metaanalysis. The main characteristics and the overall quality of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Older age [Kolte 2018;Amat-Santos 2015;Bjursten 2019;Fauchier 2020;Tabata 2020;Butt 2019;Regueiro 2016] was associated with a lower risk of PVE after TVAR (RR 0.97, 95% CI: 0.95 to 0.99, P = .007), and men sex [Kolte 2018;Amat-Santos 2015;Olsen 2015;Bjursten 2019;Fauchier 2020;Tabata 2020;Butt 2019;Regueiro 2016] was identified as a predictor of PVE after TVAR (RR 1.53, 95% CI: 1.24 to 1.90, P = .0001), while diabetes [Kolte 2018;Amat-Santos 2015;Olsen 2015;Bjursten 2019;Fauchier 2020;Tabata 2020;Butt 2019;Regueiro 2016] (RR 1.08, 95% CI: 0.86 to 1.35, P = .51), COPD [Kolte 2018; 2).…”
Section: Baseline Characteristics-related Factorsmentioning
confidence: 99%
“…In patients at high baseline surgical risk, surgery may be contraindicated, or, in any case, the presence of the supporting stent makes the surgical procedure more complex. Some studies have analyzed the incidence of IETAVI, both in Spain [2,3] and in other countries [4][5][6]. They all agree on an annual incidence of approximately 1.4-1.6% and high mortality, ranging from 41.8% in the Swedish registry of Bjursten et al [4] to 47.2% in the Spanish multicenter study by Amat-Santos et al [3].…”
mentioning
confidence: 92%
“…They also agree with regard to a high mean age of around 80 years, greater comorbidity (higher incidence of renal failure, previous cancer, higher Charlson index, etc. ), and the finding of enterococci, Staphylococcus aureus and coagulase-negative staphylococci as the most frequent microorganisms involved [2][3][4][5][6].…”
mentioning
confidence: 99%
See 1 more Smart Citation